(3QSGdI aj GdSjQI hGdehdO GdfHhjs - (3eMeO Hf CMeO Hf Ydj Hf LGHQ GdCfOdSj GdghGQj GdeGdcj, CHh YHO Gddg, TeS GdOjf,J (B780 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NJe HeMeO Udi Gddg Ydjg hSde fXGe GdeQSdjf hLYd ehdOg QMekI ddYGdejf , cGf CcQe GdNdGFb CekG hCHkG s
(3BNQgG (B:s
(3Udi GdEdg UdGI dG faGOdgG Ydi GdfHi hCUMGH dg fLH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B10 - (3U(B11s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B201 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs